Search Externalities in Firm-to-Firm Trade - Spray, John (IMF Working Papers; Working Paper, 2021)
I develop a model of firm-to-firm search and matching to show that the impact of falling trade costs on firm sourcing decisions and consumer welfare depends on the relative size of search externalities in domestic and international markets. These externalities can be positive if firms share information about potential matches, or negative if the market is congested. Using unique firm-to-firm transaction-level data from Uganda, I document empirical evidence consistent with positive externalities in international markets and negative externalities in domestic markets. I then build a dynamic quantitative version of the model and show that, in Uganda, a 25% reduction in trade costs led to a 3.7% increase in consumer welfare, 12% of which was due to search externalities.